Assessment of knowledge and perceptions of dental students about Molar-Incisor Hypomineralization (Research, Society and Development, 2022)
Objectives: To evaluate the knowledge and perceptions of dental students about Molar-Incisor Hypomineralization (MIH). Methodology: A semi-structured electronic questionnaire composed of 3 sociodemographic questions and 13 multiple-choice questions was applied to 80 undergraduate students from the School of Dentistry of the Federal University of Amazonas regularly enrolled in the fifth to a ninth period about the level of knowledge about diagnosis etiology and treatment of MIH, whose total score ranged from 1 to 36. The collected data were statistically analyzed, and the t-student, Shapiro-Wilk, Mann-Whitney, and chi-square tests were used to analyze quantitative and categorical data (p